Validation of a protocol of nursing interventions for people with anorectal diseases requiring ambulatory surgery: A clinical tool for perioperative nursing practice in the Canadian context - Mustelier Duanes, Yaquelin (Operating Room Nurses Association of Canada Journal, 2026)
Background: Nursing intervention protocols are essential to ensuring high-quality, and evidence-based care in ambulatory surgery. For individuals with anorectal diseases, standardized nursing interventions can improve surgical outcomes, reduce variability in care, support perioperative nursing practice, provide guidance in complex surgical pathways, and assist nurses working in unfamiliar or rotating surgical environments, while enhancing patient experiences through humanized, person-centred care. Methods: A methodological study using the Delphi technique was conducted to validate a protocol of nursing interventions for people with anorectal diseases requiring ambulatory surgery. Thirty-three experts in ambulatory surgery and coloproctology evaluated the protocol through successive rounds, reviewing items related to the complete perioperative process. Results: A high level of consensus was achieved in all rounds, exceeding the predefined agreement threshold of 80%. Experts rated the protocol as “very adequate” (86.07%) and “quite adequate” (4.01%). These findings indicate strong expert consensus on the protocol’s clarity, relevance, and feasibility in ambulatory surgical settings, supporting decision-making and promoting efficient, individualized nursing care throughout all perioperative phases. Conclusion: This study presents the validation of a protocol of nursing interventions for people with anorectal diseases requiring ambulatory surgery—a clinical tool for perioperative nursing practice in the Canadian context, evaluated and confirmed through expert consensus. The process highlights the protocol’s strength, coherence, clinical feasibility, and suitability for guiding perioperative nursing practice. As a validated framework, it may serve as a reference for developing ambulatory surgery nursing protocols and as a guide for perioperative nursing practice and professionals in diverse healthcare contexts, including the Canadian healthcare system.